Draft Annual Plan 1993-94. Vol-II - Planning Commission (Planning Commission, 1993)
The economy of the State is basically agrarian and more than 70% of the population depends on Agriculture for their livelihood. Agriculture contributes a major share of the income of the State. As per 1981 Agri Census, 59.1% of the holding (1.95 lakh Hectare) is occupied by small and Marginal Farmers group having less than two hectares of land. The average size of holding is about 1.87 ha. out of total geographical area of the State which is 10.491 sq. kilo-mitre (10,49,169 hectare), only 27% area is under cultivation. There is not much scope to bring further area under cultivation without necessary relaxation of the provision of the central Forest Act.
Planning and Coordination Department Government of Tripura
Planning and Coordination Department Government of Tripura